Pete the Cat and the new guy - Dean, Kim, 1969- (New York: Harper, 2014)
Pete the Cat and his animal friends welcome Gus the Platypus, who discovers his own special talent.
K-3
AD510L
2.0
Keywords: Stories in rhyme; Cats -- Fiction; Platypus -- Fiction; Animals -- Fiction; Friendship -- Fiction; Individuality -- Fiction; Ability -- Fiction